2002
DOI: 10.1207/s15327027hc1401_6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Organ Donor Card: The Effect of Knowledge, Attitudes, and Values on Willingness to Communicate About Organ Donation to Family Members

Abstract: Although numerous studies have examined many of the predictors of signing an organ donor card, including knowledge, attitudes, values, and demographic variables, very few have examined the factors associated with individuals' willingness to communicate about organ donation with family members. Because organ donation does not take place without the permission of a person's next-of-kin, government agencies and organ procurement organizations have targeted communication with family members as a primary objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
2
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(192 citation statements)
references
References 19 publications
6
167
2
17
Order By: Relevance
“…Although a spouse provides an available and easy collaborator for compliance with this request, no studies in the literature were found to have reported a significant relationship between marital status and willingness to donate marrow. Considerable research has indicated that the intention to donate solid organs and signing of organ donor cards is related to the willingness to talk to family members about organ donation, 20,21 but this research is largely based on the premise that talking to family members is particularly important for prospective solid organ donors because of the potential need for nextof-kin consent. Thus, although solid organ donation studies are not completely analogous, the mechanism that personal donor registration experiences can increase the intention to speak with family members about the process presents a potentially fruitful and inexpensive means for recruiting prospective donors into marrow donation registries that seem to have been largely ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Although a spouse provides an available and easy collaborator for compliance with this request, no studies in the literature were found to have reported a significant relationship between marital status and willingness to donate marrow. Considerable research has indicated that the intention to donate solid organs and signing of organ donor cards is related to the willingness to talk to family members about organ donation, 20,21 but this research is largely based on the premise that talking to family members is particularly important for prospective solid organ donors because of the potential need for nextof-kin consent. Thus, although solid organ donation studies are not completely analogous, the mechanism that personal donor registration experiences can increase the intention to speak with family members about the process presents a potentially fruitful and inexpensive means for recruiting prospective donors into marrow donation registries that seem to have been largely ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Among African Americans in particular, studies using a composite measure of knowledge demonstrate that overall knowledge about organ donation is an important predictor of willingness to donate [6,26,[38][39][40][41]. However, less research has explored how different types of knowledge relate to donation intentions among African Americans.…”
Section: Lack Of Knowledge As a Barrier To Donation Among African Amementioning
confidence: 99%
“…This is in keeping with the findings of Morgan and Miller for adults; of those who had signed their donor card, most had discussed their wishes with family members. 14 In our present study, parents also gave different reasons for not starting a discussion on this topic. One reason given was that they had never thought about the possibility of donation by their child.…”
Section: Discussionmentioning
confidence: 71%